The development of an authentic assessment instrument to measure students skills in learning biology in grade 8 junior high school - P D Yuniawan (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Authentic assessment in the 2013 Curriculum is echoed for all lessons. The 2013 Curriculum emphasizes that student was expected to have knowledge competence, skill competence, and attitude competence. This research was conducted to develop authentic assessment instruments in the implementation of the final assessment of the school, especially on the skills aspect so as to obtain valid, practical, and effective assessment instruments. This assessment instrument research uses a 4-D development model. The objective of the research is the skill aspect assessment instrument that was tested on 34 graders 8 Junior High School in the first semester with the experimental “One Shot Case Study” model. Data analysis using descriptive qualitative. The result of data analysis showed: validation of skill assessment instruments was a very valid (3.56), readability of assessment instruments in categories was interesting and easy to understand, implementation of the assessment instruments entered in a very good category with a very high percentage (97,92%), reliability showed a reliable result (r>0.70). It can be concluded that the development of authentic assessment instruments to measure students skills in learning biology grade 8 junior high schools was valid, practical, and effective.